Frequency of F116-mediated transduction of Pseudomonas aeruginosa in a freshwater environment. - Morrison, W D (1978)
Transduction of Pseudomonas aeruginosa streptomycin resistance by a generalized transducing phage, F116, was shown to occur during a 10-day incubation in a flow-through environmental test chamber suspended in a freshwater reservoir. Mean F116 transduction frequencies ranged from 1.4 X 10(-5) to 8.3 X 10(-2) transductants per recipient during the in situ incubation. These transduction frequencies were comparable to transduction frequencies determined in preliminary laboratory transduction experiments. The results demonstrate the potential for naturally occurring transduction in aquatic environments and concurrent environmental and ecological ramifications.